THE EFFECT OF GRAPHIC ORGANIZERS AND READING ATTITUDE ON THE FIFTH GRADE PUPILS’ READING COMPREHENSION OF PALM KIDS ELEMENTARY SCHOOL, PALEMBANG - Inda Arintina (Universitas PGRI Palembang, 2019)
AbstractThe thesis was concerned on the inquiry on the effect of Graphic Organizers and reading attitude on the fifth grade pupils’ reading comprehension of Elementary School Palm Kids, Palembang. The problem of this study was to find out whether or not there was significant effect of Graphic Organizers on the fifth grade pupils’ reading comprehension of Elementary School Palm Kids, Palembang. Graphic Organizers is a visual communication tool that uses visual symbols to express ideas and concepts, to convey meaning. Data collection employed pretest and posttest for experimental and control classes. Data analysis was undertaken by using paired sample t-test, independent sample t-test, and Two-way ANOVA. Findings showed that there was significant effect of Graphic Organizers and reading attitude on the fifth grade pupils’ reading comprehension of Elementary School Palm Kids, Palembang. Conclusion suggests that the alternative hypothesis (Ha) was accepted while the nul hypothesis (Ho) was rejected. It means that Graphic Organizers was effective to improve pupils’ reading comprehension.Keywords: Graphic Organizers, Reading Attitude, and Reading Comprehension